CONGENITAL MALFORMATIONS: PRENATAL DIAGNOSTICS AND NOVEL CONCEPTION OF MEDICAL HELP TO NEWBORNS - Yu.F. Isakov; V.I. Kulakov; Yu.I. Kucherov ("Paediatrician" Publishers LLC, 2007)
Current views on basic prenatal diagnostics techniques, as ultrasound, maternal serum biochemical markers (alpha fetoprotein, human chorionic gonadotropin, and unconjugated estriol), and fetal biologic material (chorionic villus sampling, placenta, amniotic liquid, fetal blood), obtained with invasive techniques (chorion biopsy, amniocentesis, cordocentesis), its' efficacy and possible practical application are given in the article. These new conception announce to consolidate three branches providing maternal and children - welfare should consolidate maternal welfare outpatient clinics, maternal hospital and newborn surgery hospital - into one institute, thus allowing to success work of all stages, to avoid transportation and late surgical treatment, to reduce lethal outcomes following surgical treatment of congenital malformations. Primary results of implementation of this conception are presented in the article.Key words: prenatal diagnostics, newborns, congenital mal formations, prevention and prophylactics, diagnostics.